Circulating Monocytes Serve as Novel Prognostic Biomarker in Pancreatic Ductal Adenocarcinoma Patients - Hansen, Frederik; David, Paul; Akram, Marina; Knoedler, Samuel; Mittelstädt, Anke; Merkel, Susanne; Podolska, Malgorzata; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; Kouhestani, Dina; Anthuber, Anna; et al. (Cancers, 2023)
Pancreatic ductal adenocarcinoma (PDAC) ranks among the most fatal cancer diseases, widely accepted to have the most dismal prognoses. Although immunotherapy has broadly revolutionized cancer treatment, its value in PDAC appears to be relatively low. Exhibiting protumoral effects, monocytes have recently been proposed as potential targets of such immunotherapeutic regimens. However, to date, the body of evidence on monocytes’ role in PDAC is scarce. Therefore, we analyzed monocytes in the peripheral blood of 58 PDAC patients prior to surgery and compared them to healthy individuals. PDAC patients showed increased levels of monocytes when compared to healthy controls In addition, patients with perineural infiltration demonstrated a higher percentage of monocytes compared to non-infiltrating tumors and PDAC G3 was associated with higher monocyte levels than PDAC G2. Patients with monocyte levels > 5% were found to have an 8.9-fold increased risk for a G3 and perineural infiltrated PDAC resulting in poorer survival compared to patients with <5% monocyte levels. Furthermore, PDAC patients showed increased expressions of CD86 and CD11c and decreased expressions of PD-L1 on monocytes compared to healthy individuals. Finally, levels of monocytes correlated positively with concentrations of IL-6 and TNF-α in plasma of PDAC patients. Based on our findings, we propose monocytes as a novel prognostic biomarker. Large-scale studies are needed to further decipher the role of monocytes in PDAC and investigate their potential as therapeutic targets.
CRIS-Team Scopus Importer:2023-02-03
Keywords: grading; liquid biopsy; monocytes; pancreatic ductal adenocarcinoma; perineural invasion; prognostic biomarker

Current Applications of Liquid Biopsy in Gastrointestinal Cancer Disease—From Early Cancer Detection to Individualized Cancer Treatment - David, Paul; Mittelstädt, Anke; Kouhestani, Dina; Anthuber, Anna; Kahlert, Christoph; Sohn, Kai; Weber, Georg (Cancers, 2023)
Worldwide, gastrointestinal (GI) cancers account for a significant amount of cancer-related mortality. Tests that allow an early diagnosis could lead to an improvement in patient survival. Liquid biopsies (LBs) due to their non-invasive nature as well as low risk are the current focus of cancer research and could be a promising tool for early cancer detection. LB involves the sampling of any biological fluid (e.g., blood, urine, saliva) to enrich and analyze the tumor’s biological material. LBs can detect tumor-associated components such as circulating tumor DNA (ctDNA), extracellular vesicles (EVs), and circulating tumor cells (CTCs). These components can reflect the status of the disease and can facilitate clinical decisions. LBs offer a unique and new way to assess cancers at all stages of treatment, from cancer screenings to prognosis to management of multidisciplinary therapies. In this review, we will provide insights into the current status of the various types of LBs enabling early detection and monitoring of GI cancers and their use in in vitro diagnostics.
CRIS-Team Scopus Importer:2023-04-28
Keywords: circulating tumor cells (CTCs); circulating tumor DNA (ctDNA); gastrointestinal cancer; liquid biopsy; organoids; tumor exosomes; tumor-educated blood platelets (TEPs)

Discrimination of pancreato-biliary cancer and pancreatitis patients by non-invasive liquid biopsy - Hartwig, Christina; Müller, Jan; Klett, Hagen; Kouhestani, Dina; Mittelstädt, Anke; Anthuber, Anna; David, Paul; Brunner, Maximilian; Jacobsen, Anne; Glanz, Karolina; Swierzy, Izabela; Roßdeutsch, Lotta; et al. (Molecular Cancer, 2024)
Background: Current diagnostics for the detection of pancreato-biliary cancers (PBCs) need to be optimized. We therefore propose that methylated cell-free DNA (cfDNA) derived from non-invasive liquid biopsies serves as a novel biomarker with the ability to discriminate pancreato-biliary cancers from non-cancer pancreatitis patients. Methods: Differentially methylated regions (DMRs) from plasma cfDNA between PBCs, pancreatitis and clinical control samples conditions were identified by next-generation sequencing after enrichment using methyl-binding domains and database searches to generate a discriminatory panel for a hybridization and capture assay with subsequent targeted high throughput sequencing. Results: The hybridization and capture panel, covering around 74 kb in total, was applied to sequence a cohort of 25 PBCs, 25 pancreatitis patients, 25 clinical controls, and seven cases of Intraductal Papillary Mucinous Neoplasia (IPMN). An unbiased machine learning approach identified the 50 most discriminatory methylation markers for the discrimination of PBC from pancreatitis and controls resulting in an AUROC of 0.85 and 0.88 for a training (n = 45) and a validation (n = 37) data set, respectively. The panel was also able to distinguish high grade from low grade IPMN samples. Conclusions: We present a proof of concept for a methylation biomarker panel with better performance and improved discriminatory power than the current clinical marker CA19-9 for the discrimination of pancreato-biliary cancers from non-cancerous pancreatitis patients and clinical controls. This workflow might be used in future diagnostics for the detection of precancerous lesions, e.g. the identification of high grade IPMNs vs. low grade IPMNs.
CRIS-Team Scopus Importer:2024-02-16
Keywords: cfDNA; cfMBD-Seq; DMRs; Hybridization and capture; IPMN; Methylation; Next-generation sequencing; Non-invasive diagnostics; Pancreatitis; Pancreato-biliary cancer

Exosomal ROR1 in peritoneal fluid identifies peritoneal disseminated PDAC and is associated with poor survival - Mittelstädt, Anke; Anthuber, Anna; David, Paul; Podolska, Malgorzata; Benard, Alan; Brunner, Maximilian; Krautz, Christian; Jacobsen, Anne; Denz, Axel; Weber, Klaus; Merkel, Susanne; Hackner, Danilo; et al. (Frontiers in Immunology, 2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest forms of cancer and peritoneal dissemination is one major cause for this poor prognosis. Exosomes have emerged as promising biomarkers for gastrointestinal cancers and can be found in all kinds of bodily fluids, also in peritoneal fluid (PF). This is a unique sample due to its closeness to gastrointestinal malignancies. The receptor tyrosine kinase-like orphan receptor 1 (ROR1) has been identified as a potential biomarker in human cancers and represents a promising target for an immunotherapy approach, which could be considered for future treatment strategies. Here we prospectively analyzed the exosomal surface protein ROR1 (exo-ROR1) in PF in localized PDAC patients (PER-) on the one hand and peritoneal disseminated tumor stages (PER+) on the other hand followed by the correlation of exo-ROR1 with clinical-pathological parameters. Methods: Exosomes were isolated from PF and plasma samples of non-cancerous (NC) (n = 15), chronic pancreatitis (CP) (n = 4), localized PDAC (PER-) (n = 18) and peritoneal disseminated PDAC (PER+) (n = 9) patients and the surface protein ROR1 was detected via FACS analysis. Additionally, soluble ROR1 in PF was analyzed. ROR1 expression in tissue was investigated using western blots (WB), qPCR, and immunohistochemistry (IHC). Exosome isolation was proven by Nano Tracking Analysis (NTA), WB, Transmission electron microscopy (TEM), and BCA protein assay. The results were correlated with clinical data and survival analysis was performed. Results: PDAC (PER+) patients have the highest exo-ROR1 values in PF and can be discriminated from NC (p <0.0001), PDAC (PER-) (p <0.0001), and CP (p = 0.0112). PDAC (PER-) can be discriminated from NC (p = 0.0003). In plasma, exo-ROR1 is not able to distinguish between the groups. While there is no expression of ROR1 in the exocrine pancreatic tissue, PDAC and peritoneal metastasis show expression of ROR1. High exo-ROR1 expression in PF is associated with lower overall survival (p = 0.0482). Conclusion: With exo-ROR1 in PF we found a promising diagnostic and prognostic biomarker possibly discriminating between NC, PDAC (PER-) and PDAC (PER+) and might shed light on future diagnostic and therapeutic concepts in PDAC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: biomarker; exosomes; PDAC; peritoneal carcinomatosis; peritoneal fluid; peritoneal lavage; ROR1; targeted therapy

Interleukin-3 is a predictive marker for severity and outcome during SARS-CoV-2 infections - Bénard, Alan; Jacobsen, Anne; Brunner, Maximilian; Krautz, Christian; Klösch, Bettina; Swierzy, Izabela; Naschberger, Elisabeth; Podolska, Malgorzata; Kouhestani, Dina; David, Paul; Birkholz, Torsten; Castellanos, Ixchel; et al. (Nature Communications, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide health threat. In a prospective multicentric study, we identify IL-3 as an independent prognostic marker for the outcome during SARS-CoV-2 infections. Specifically, low plasma IL-3 levels is associated with increased severity, viral load, and mortality during SARS-CoV-2 infections. Patients with severe COVID-19 exhibit also reduced circulating plasmacytoid dendritic cells (pDCs) and low plasma IFNα and IFNλ levels when compared to non-severe COVID-19 patients. In a mouse model of pulmonary HSV-1 infection, treatment with recombinant IL-3 reduces viral load and mortality. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating pDCs into the airways by stimulating CXCL12 secretion from pulmonary CD123+ epithelial cells, both, in mice and in COVID-19 negative patients exhibiting pulmonary diseases. This study identifies IL-3 as a predictive disease marker for SARS-CoV-2 infections and as a potential therapeutic target for pulmunory viral infections.
CRIS-Team Scopus Importer:2021-03-05

Tumor Infiltration with CD20+CD73+ B Cells Correlates with Better Outcome in Colorectal Cancer - Hansen, Frederik; Wu, Zhiyuan; David, Paul; Mittelstädt, Anke; Jacobsen, Anne; Podolska, Malgorzata; Ubieta Hernández, Kenia; Brunner, Maximilian; Kouhestani, Dina; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; et al. (International Journal of Molecular Sciences, 2022)
Immunotherapy has become increasingly important in the treatment of colorectal cancer (CRC). Currently, CD73, also known as ecto-5′-nucleotidase (NT5E), has gained considerable interest as a potential therapeutic target. CD73 is one of the key enzymes catalyzing the conversion of extracellular ATP into adenosine, which in turn exerts potent immune suppressive effects. However, the role of CD73 expression on various cell types within the CRC tumor microenvironment remains unresolved. The expression of CD73 on various cell types has been described recently, but the role of CD73 on B-cells in CRC remains unclear. Therefore, we analyzed CD73 on B-cells, especially on tumor-infiltrating B-cells, in paired tumor and adjacent normal tissue samples from 62 eligible CRC patients. The highest expression of CD73 on tumor-infiltrating B-cells was identified on classswitched memory B-cells, followed by naive B-cells, whereas no CD73 expression was observed on plasmablasts. Clinicopathological correlation analysis revealed that higher CD73+ B-cells infiltration in the CRC tumors was associated with better overall survival. Moreover, metastasized patients showed a significantly decreased number of tumor-infiltrating CD73+ B-cells. Finally, neoadjuvant therapy correlated with reduced CD73+ B-cell numbers and CD73 expression on B-cells in the CRC tumors. As promising new immune therapies are being developed, the role of CD73+ B-cells and their subsets in the development of colorectal cancer should be further explored to find new therapeutic options.
CRIS-Team Scopus Importer:2022-05-20
Keywords: B-cells; CD20; CD73; colorectal cancer; neoadjuvant treatment